Comentario crítico de la reforma a la ley estatutaria de salud del año 2013 - Díaz Gutiérrez, Iván Alberto (2023)
After Law 100 was passed in 1993, this act has been amended by many regulatory decrees, as well as several legal and constitutional reforms. This has been done with the intention of solving various problems that affect the general public, the medical profession, the financial sector, and the state as the healthcare system’s regulator. A new statutory law approved by Congress seeks to provide new solutions to these problems. This article critically a nalyzes the content of this law and draws conclusions on whether this law solves the problems of Colombia’s healthcare system